LABOR MIGRATION IN KYRGYZSTAN - ELEBAEVA, Ainura (CENTRAL ASIA AND THE CAUCASUS, 2004)
Due to various social-economic factors typical of the transition period that followed the Soviet Un-ion’s disintegration legal and illegal labor migration is one of the main methods of job- hunting in the republic. The demographic situation is another factor especially obvious in the south—the most populated and demographically overburdened area in the post-Soviet expanse. In this area, children and teenagers under 16 account for about 40 percent of population; young people between 16 and 29 constitute 50 per-cent of the workforce; and people over 60 make up 7-8 percent of the total population. Every year large numbers of young people flock to the labor market in search of a job, thus adding to its already consider-able demographic pressure. Obviously, employment problems are hard to resolve, especially at the transition stage when eco-nomic development slows down. In the 1990s industrial production in the republic dropped by nearly half. According to the First National Population Census of 1999 in 10 years the employment level in cities fell from 66.5 to 42.2 percent; the figures for the country being 67.3 and 64 percent; and the share of depend-ents increased from 12 to 24.8 percent.1 Unemployment forces people to leave their country in search of work; in transitional economies migration somewhat alleviates the pressure on the labor market and inflation and compensates for the lowered incomes; it makes it possible to avoid a dramatic drop in the living standards of a large number of people. Like many of its CIS neighbors, the Republic of Kyrgyzstan (RK) is a host country to the migrant workers and is itself a source of labor migrants. It exports more workers than it imports. The titular population predominates in the workforce outflow, especially to CIS countries. On the whole, labor outflow from our country is large-scale and mainly haphazard. Its main flows are temporary migrants prefer to come back. There are no reliable statistics of the process in the republic—official figures have little in common with reality. Art 16 of the RK Constitution envisages the right to labor; this right is specified in the Labor Code, which enumerates the rules and conditions of labor and the guarantees of labor-related rights.he Law on Licensing Certain Types of Activity and governmental decisions in this field regulate the labor market together with the Code and the main legal acts related to foreign labor migration.he rights of our citizens working abroad are protected by the recently signed intergovernmental documents. There are regional agreements among the Central Asian countries and agreements with other CIS states. The largest number of such documents was signed with Russia; they are On Protecting the Rights of Working Migrants, On Mutual Recognition of Diplomas and Academic Degrees, etc. Similar documents were signed with Kazakhstan, Uzbekistan, Tajikistan, and Azerbaijan. There are cooperation programs with the WTO and the International Migration Organization.